Formation of the snow isotopic composition on the Arctic glaciers (case study of Spitsbergen and Severnaya Zemlya) - V. I. Nikolaev; N. N. Osokin; E. P. Zazovskaya (Лëд и снег, 2015)
Stable isotope studies of snow cover along several itineraries through Spitsbergen were carried out (from Gronfjorden coast till ice divide of Gronfjord – Fridtjov glacier and from Barentsburg settlement till Olav mountain). Results obtained were compared with ones fixed for snow on Severnaya Zemlya archipelago. Uncertainty of condensation processes were shown for precipitation falling on Arctic polar ice domes (sometimes we fixed altitudinal isotope gradient and in other cases the gradient was absent). In periglacial zone of arctic islands isotope values are scattered randomly, covering the entire annual precipitation range due to strong snow-storms.